New Multidrug Efflux Inhibitors for Gram-Negative Bacteria - Marshall, Robert L. (mBio, 2020)
Active efflux of antibiotics preventing their accumulation to toxic intracellular concentrations contributes to clinically relevant multidrug resistance. Inhibition of active efflux potentiates antibiotic activity, indicating that efflux inhibitors could be used in combination with antibiotics to reverse drug resistance. Expression of ramA by Salmonella enterica serovar Typhimurium increases in response to efflux inhibition, irrespective of the mode of inhibition. We hypothesized that measuring ramA promoter activity could act as a reporter of efflux inhibition. A rapid, inexpensive, and high-throughput green fluorescent protein (GFP) screen to identify efflux inhibitors was developed, validated, and implemented. Two chemical compound libraries were screened for compounds that increased GFP production. Fifty of the compounds in the 1,200-compound Prestwick chemical library were identified as potential efflux inhibitors, including the previously characterized efflux inhibitors mefloquine and thioridazine. There were 107 hits from a library of 47,168 proprietary compounds from L. Hoffmann La Roche; 45 were confirmed hits, and a dose response was determined. Dye efflux and accumulation assays showed that 40 Roche and three Prestwick chemical library compounds were efflux inhibitors. Most compounds had specific efflux-inhibitor-antibiotic combinations and/or species-specific synergy in antibiotic disc diffusion and checkerboard assays performed with Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Salmonella Typhimurium. These data indicate that both narrow-spectrum and broad-spectrum combinations of efflux inhibitors with antibiotics can be found. Eleven novel efflux inhibitor compounds potentiated antibiotic activities against at least one species of Gram-negative bacteria, and data revealing an E. coli mutant with loss of AcrB function suggested that these are AcrB inhibitors.